Harnessing AI for Entrepreneurs: Big Data’s Role in Social Innovation - L Lanuwabang, Anubhav Tiwari, Aayushi Arya, N. Yashan (Journal of Informatics Education and Research, 2024)
In today's fast-changing world of tech and business, AI has become a game-changer for entrepreneurs. It's reshaping how they make choices and come up with new ideas. When AI teams up with big data analysis, it opens up a whole new world for business owners. It gives them super-smart insights and tools to tackle tough problems. This mix of AI and big data in business is key. This article explores the complexities of big data and AI explaining why big data matters to entrepreneurs and how they can use this technology to their benefit. It examines how big data can spark social innovation looking at both its possibilities and problems. The text also considers how AI plays a key role in boosting social entrepreneurship and predicts what's next for AI big data, and entrepreneurship. By giving a full picture, this piece aims to help entrepreneurs and business leaders to understand how to use big data and AI to make choices and come up with new ideas helping their businesses grow and succeed.